Does money grow on trees? : the role of climate change finance in South Africa. - Newmarch, Jocelyn (My University, 2013)
Rapid, human-forced climate change as a result of greenhouse gases is threatening the fabric of human civilisation itself. It is clear that we need to alter our development and poorer countries will need to develop while limiting their emissions, but it is not clear what sustainable development would entail. Climate change policy solutions have pivoted on carbon trading, under the auspices of the Clean Development Mechanism (CDM), but this too has failed to limit growth in carbon emissions. This report looks at the operations of the CDM in South Africa as a source of climate finance meant to facilitate sustainable development. Though South Africa has emphasised its commitment towards a low-carbon transition, in practice its national planners seek to preserve energy-intensive mineral and industrial sectors. This research draws on both primary and secondary documents as well as interviews with carbon professionals to conclude that CDM projects have played a limited role in South Africa, but has tended to reproduce the existing minerals and energy complex within the country.
Keywords: Climatic changes--Economic aspects--South Africa.; Environmental policy--Economic aspects--South Africa.; Carbon offsetting--South Africa.; Greenhouse gases--South Africa.